The influence of transverse shearing and rotatory inertia on the vibrations of fibrous composite beam - Gołaś, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper was to determine the influence of transverse shear deformation and rotatory inertia on the natural frequencies and on the values of displacements of beams made of fibrous composites reinforced with layers' of long fibres. It was assumed that the matrix of the composite beam possesses linear elastic and transversaIly isotropic properties.
Keywords: dźwigary; drgania; odkształcenia; dynamics of composite beam; transverse shear effect